Implikasi Hukum dalam Penanganan Kredit Bermasalah: Perspektif OJK di Indonesia - Tobing, Ruben Nicholas Alfredo; Allenvidia, Fabian Beryl (Media Hukum Indonesia (MHI), 2024)
Non-Performing Loans (NPL) are one of the main issues affecting the stability of the banking system in Indonesia. This article examines the legal implications in handling non-performing loans through an analysis of regulations issued by the Financial Services Authority (OJK) and an evaluation of the implementation of these regulations in banking practices. The study uses a normative legal method with a statutory regulatory approach, supported by relevant case studies. The results of the study indicate that the main obstacles in resolving NPLs include limited human resources, the complexity of the legal process, and challenges in executing collateral. This article recommends improving regulations, strengthening the capacity of financial institutions, and more effective collaboration between regulators and industry players to increase the effectiveness of NPL resolution and maintain national banking stability.